Prognostication of poor obstetric outcomes by biochemical first trimester screening resalts - I O Makarov; E V Yudina; E I Borovkova; E I Kirpikova (RUDN Journal of Medicine, 2011)
We identified 158 patients with first-trimester PAPP-A and b-HCG < 5th centile. We excluded multiple pregnancies and major anomalies. 15,2% had evidence of fetal growth restriction and had significantly higher rates of gestational hypertension, preterm birth, low birth weight, 1-min Apgar score < 7, neonatal intensive care.